POTENSI UMKM BATIK PARIJOTO KUDUS SEBAGAI PENDUKUNG EKONOMI GUNA MEWUJUDKAN SDGS MENUJU MEGATREND 2045 - Septiana, Lisa; Addiansyah, M. Rofiq (ANALISIS, 2024)
Indonesia is a country where UMKM are experiencing significant changes and it is estimated that in the next twenty years there will be major changes. This is proven by the number of global middle income classes which is predicted to increase by 4.9 billion by 2045. One area with a number of MSMEs that have entered the product projection stage is Kudus Regency, where out of thousands of MSMEs, 15 business actors can export abroad. According to the KBBI, megatrend means a big trend in style. In other words, a megatrend is a trend that has an impact on a large scale. Megatrend can also be interpreted as a major change in social, economic, political and technological aspects that is slow to form and after this change occurs, it can have an influence over a long period of time. The aim is to be able to prioritize digital economic transformation and be a reference for further research. This paper uses a qualitative method by taking a descriptive approach. At the data collection stage, the author collects various types of information related to the topics discussed through online platforms such as journals, books and papers, as well as other supporting data so that it is optimal if used as material for consideration. Then, the results of this research are as economic support, namely the Kudus Parijoto batik MSMEs trying to be present in building a quality next generation of the nation, especially preserving the sustainable local wisdom of the Kudus community. The following are several government actors who participate in supporting the economy of the Kudus community through Parijoto batik MSMEs, including the Ministry of Cooperatives, Small and Medium Enterprises, the Ministry of Industry, and the Ministry of Industry. The hope is that it will be able to improve the quality of human resources, thus helping them be more independent with the knowledge they have acquired and participate in boosting the economy of each family. Keywords: UMKM, Networking Management, SDG's